Student Passivity and Classroom Participation in EFL Classrooms: Teachers' Perspectives on Contributing Factors and Instructional Strategies in Aceh, Indonesia - Rahmi, Rahmi; Hasnati, Ihya (LETS: Journal of Linguistics and English Teaching Studies, 2026)
This study investigated teachers’ perceptions of the factors contributing to student passivity in English as a Foreign Language (EFL) classrooms and the strategies they employed to promote active classroom participation in Aceh, Indonesia. Adopting a qualitative descriptive design, data were collected through semi-structured interviews with five EFL teachers from two junior high schools in Southwest Aceh. The interview data were analyzed using the interactive model of data analysis proposed by Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. The findings revealed that teachers generally conceptualized student passivity as limited behavioral engagement characterized by silence, reluctance to respond, and low involvement in classroom activities. Teachers identified psychological, linguistic, motivational, and contextual factors as contributing to student passivity. To address this issue, teachers reported implementing collaborative group work, game-based learning activities, and technology-enhanced instruction. These findings demonstrate how teachers interpreted the causes of student passivity and responded through instructional practices aimed at increasing participation. This study contributes to the EFL literature by providing context-specific insights into student passivity in Aceh, an underexplored educational setting, and by demonstrating how teachers interpreted and responded to passive participation. The findings offer practical implications for EFL teachers, teacher educators, and policymakers seeking to foster more active classroom participation.